L’Effet des Pratiques Ressources Humaines sur la Performance Organisationnelle des Communes au Cameroun - Bandibeno, Innocents Kollo; Nkonga, Liliane (European Scientific Journal, ESJ, 2018)
This article examines the perceived quality of HR practices on the organizational performance of municipalities. The study showed that the quality of human resources practices has a positive effect on the organizational performance of the municipalities. The results of this work make it possible to consider on the one hand a strengthening of the control mechanisms in the recruitment procedure and on the other hand to elaborate a career plan of the municipal staff. In addition, joint regulation between the various divisions is an asset for organizational performance. Thus, the quality of HR practices underlies organizational performance.